The Arts as Education: Why Arts Education should be Included in the Curricular Area - Puri, Anjana (JOURNAL OF INDIAN EDUCATION, 2007)
Although the arts are as old as mankind and are as complex as the ways of human beings, they have not yet been given the same status as the sciences and the humanities have been given, within the frame of school education. One has yet to understand the inherent link that connects the arts to other subjects, giving them their inter-disciplinary character. Each of the arts – irrespective of whether they are performing, non-performing, visual – has inherent values that make it a source for education, holistic in nature. It thus becomes significant to examine performance holistically, because within the concept of holistic performance are a large number of areas that might be diverse in nature, but are closely linked to each other within as well as outside the bounds of the art form. It is, therefore, required to look for the relationship between the performing arts and the other subjects. One could investigate to what extent the arts have been integrated in the text of specific subject areas or one could look for different subject areas in the performing and visual arts. This would need analysing the arts in a manner that would highlight various fields associated integrally with the arts. The arts have to be considered as something beyond immediate performance, comprehending the difference in concepts such as ‘arts in education’, ‘arts and education’ and ‘art as education’.